2022
DOI: 10.3389/fpubh.2022.861072
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Healing Potential of Rural Community Streets From the Perspective of Audiovisual Integration: A Case Study of Four Rural Communities in China

Abstract: Rural communities have become a hot topic in academic circles because of their graceful natural environment and great healing potential. However, existing research still lacks attention to the street space in rural communities and rarely considers its integrated visual and soundscape design in terms of their effect on public health. As a result, the healing potential of rural community streets cannot be fully used in design practice. Relevant audiovisual materials were collected from a field investigation in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…VR technology has gained increasing recognition in urban environmental cognition and experience research, and some scholars have demonstrated the feasibility of the technology in environmental health design research ( 14 , 15 ), but some scholars have recently argued that research findings in virtual natural environments are unreliable and need to be further calibrated and validated in the future ( 37 ). This study explored the effects of two landscape elements: green vegetation and fitness facilities, on the emotional health of people in residential compound space based on a virtual experimental platform, and the results showed that the residential compound space environment with a higher green view rate has a better effect on the emotional health of people, which is consistent with the previous study conducted in a real environment, which concluded that “the magnitude of the green view rate is positively correlated with emotional recovery” ( 38 , 39 ) and “higher recovery is more likely to be associated with natural rather than artificial landscape elements” ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VR technology has gained increasing recognition in urban environmental cognition and experience research, and some scholars have demonstrated the feasibility of the technology in environmental health design research ( 14 , 15 ), but some scholars have recently argued that research findings in virtual natural environments are unreliable and need to be further calibrated and validated in the future ( 37 ). This study explored the effects of two landscape elements: green vegetation and fitness facilities, on the emotional health of people in residential compound space based on a virtual experimental platform, and the results showed that the residential compound space environment with a higher green view rate has a better effect on the emotional health of people, which is consistent with the previous study conducted in a real environment, which concluded that “the magnitude of the green view rate is positively correlated with emotional recovery” ( 38 , 39 ) and “higher recovery is more likely to be associated with natural rather than artificial landscape elements” ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the natural elements, green vegetation is considered to be the most important landscape element ( 8 – 11 ), and the green view rate is considered to be the best indicator of environmental effects on stress reduction and emotional recovery (20–40% decompression effect is the best) ( 12 ). Xu et al demonstrated through VR experiments that the green view rate and openness of street interface have significant effects on street healing ( 13 ), and Fu Erkang et al also found that a high green view rate and low openness could effectively promote the perception of healing in street space in a study of audio-visual interactive street healing environment ( 14 ). In addition, positively valued man-made features play a key role in the visual quality of the environment and are an important landscape element ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Rural landscapes, which are distinguished by their unique ecological attributes and substantial restorative potential [29], are considered highly conducive to the restoration of physical and mental health in the modern world [30]. Studies have indicated that living in rural environments helps alleviate physiological stress such as tension and fatigue [31], improves emotional states, and facilitates psychological recovery [32].…”
Section: Landscape Types and Elements Of Perceived Restorativenessmentioning
confidence: 99%
“…Some studies have examined the impact of certain landscape elements on restorativeness. For example, a recent study found that rural landscapes rich in natural elements significantly enhanced people's perception of healing [29]. Nordh noted that water, terrain, and vegetation are the most restorative elements in a landscape [34].…”
Section: Landscape Types and Elements Of Perceived Restorativenessmentioning
confidence: 99%
See 1 more Smart Citation